Uji Efektivitas Ekstrak Kulit Bawang Merah Dalam Mengendalikan Kutu Kebul (Bemisia tabaci Gennadius) Pada Tanaman Cabai - Eko Aprianto; Helda Orbani Rosa; Salamiah Salamiah (www.ulm.ac.id, 2023)
Chili plants are plants that are very popular with farmers because they have high economic prices and are easy to cultivate in the highlands and lowlands. One of the chili pest attacks is the whitefly (Bemisia tabaci Gennadius) which is a virus vector that can reduce chili production. Whitefly pest control (Bemisia tabaci Gennadius) still uses chemical pesticides so that alternative controls are needed using vegetable pesticides, one of which is shallot skin extract. The treatment used in this study consisted of 5 treatments namely water control, chemical control and 3 treatments with shallot skin extract concentrations (2%, 4% and 6%) which were repeated 4 times. This study used two application methods, namely the application of shallot skin extract directly to the plant and the application of shallot skin extract directly to the test insect (Bemisia tabaci Gennadius). The results of the study showed that onion skin extract had the highest mortality, namely 27.5% by direct application to plants and 35% by direct application to test insects (Bemisia tabaci Gennadius). at the concentration of shallot skin extract 6%.